Lumiestrone is Photochemically Derived from Estrone and may be Released to the Environment without Detection - Trudeau, Vance L.; Heyne, Belinda; Blais, Jules M.; Temussi, Fabio; Atkinson, Susanna K.; Pakdel, Farzad; Popesku, Jason T.; Marlatt, Vicki L.; Scaiano, Juan C.; Previtera, Lucio; Lean, David R. (Frontiers in Endocrinology, 2011)
Endocrine disrupting chemicals are adversely affecting the reproductive health and metabolic status of aquatic vertebrates. Estrone is often the dominant natural estrogen in urban sewage, yet little is known about its environmental fate and biological effects. Increased use of UV-B radiation for effluent treatments, and exposure of effluents to sunlight in holding ponds led us to examine the effects of environmentally relevant levels of UV-B radiation on the photodegradation potential of estrone. Surprisingly, UV-B mediated degradation leads to the photoproduction of lumiestrone, a little known 13α-epimer form of estrone. We show for the first time that lumiestrone possesses novel biological activity. In vivo treatment with estrone stimulated estrogen receptor (ER) α mRNA production in the male goldfish liver, whereas lumiestrone was without effect, suggesting a total loss of estrogenicity. In contrast, results from in vitro estrogen receptor-dependent reporter gene assays indicate that lumiestrone showed relatively higher estrogenic potency with the zebrafish ERβ2 than zfERα, suggesting that it may act through an ERβ-selectivity. Lumiestrone also activated human ERs. Microarray analysis of male goldfish liver following in vivo treatments showed that lumiestrone respectively up- and down-regulated 20 and 69 mRNAs, which was indicative of metabolic upsets and endocrine activities. As a photodegradation product from a common estrogen of both human and farm animal origin, lumiestrone is present in sewage effluent, is produced from estrone upon exposure to natural sunlight and should be considered as a new environmental contaminant.